Factors Influencing Perception of Labor Pain among Parturient Women at Tribhuvan University Teaching Hospital - Shrestha, Isha; Pradhan, N; Sharma, J (Nepal Journal of Obstetrics and Gynaecology, 2013)
Aims: This study was done to understand the severity of labor pain in parturients of Kathmandu and to determine factors affecting it. Methods: A descriptive study was conducted in Tribhuvan University Teaching Hospital (TUTH), Kathmandu, Nepal where 300 term parturientsin active labor (cervical dilatation of 3-5 cm with three uterine contractions in 10 minutes each lasting for ≥ 30 seconds) were analysed for socio-demographic data, clinical profile and pain assessment.Visual analog scale was used for pain assessment. Results: The intensity of labor pain was graded as severe by 32%, moderateby 57% and mild by 11% of parturients.Almost half ofthe parturients in the age group of ≤19years described labor pain as severe as compared to women between 20-34years (30.4%) and ≥35years (20%). Among the nulliparous parturients, 37% described it as severe compared to only 20.7% in≥Para1.In those with≥higher secondary leveleducation, 35.9% described labor pain as severe as compared to those women who had education of ≤primary level(26.9%) and upto secondary level (27.1%). Labor pain was seen to be more severe in advanced labor withmore than half describingit as severe when the cervix was dilated to 5 cm, as compared to only 25.9% and 29.4% of the parturients at 3 and 4cm cervical dilatation respectively. Conclusions: This study concluded that the labor pain was moderate to severe for majority of the parturients.Adolescents, nullipara, patients with higher education and those in advanced laborwere more likely to perceive labor pain of higher intensity. Nepal Journal of Obstetrics and Gynaecology / Vol 8 / No. 1 / Issue 15 / Jan- June, 2013 / 26-30 DOI: http://dx.doi.org/10.3126/njog.v8i1.8857